Comparative analysis of the application of the modular and special object handles - Barylski, Adam (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
In the article, an attempt was made to quantify the technological structure performance of designed special and modular handles, using the indicator method. Handles for selected operations of lever machining and uniform body were analyzed. The applied methodology can be used, inter alia, in the process of engineering education of technologists mechanics. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)